On the essence of the collective ownership enterprise status - Павленко, Олександр Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Substantiated that points Order Derzhspozhivstandart Ukraine, which is not expected creation and state registration of new companies with the legal form of PCI should be canceled. It is proved that it is expedient to revive collective ownership. Collective property must occupy an intermediate position between private and public and should take the positive features of each of these other types of property, get rid of negative traits. In determining the optimal set of powers set to be embed in the legal status of PCI should be based on the so-called beam powers that offered the British lawyer A.Onore.